DESIGN AND DEVELOPMENT OF MONITORING SYSTEM APPLICATIONS LYN SEPARATION OF STTAL PERSONNEL BASED ON ANDROID SYSTEM - Suprayitno Suprayitno; Supartono Supartono; Arie Marbandi; Antonius Abdi Setiyawan (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The STTAL personnel pickup lyn mechanism and system is a means of pick-up transportation that helps STTAL personnel to transport departures from the pickup location to the work unit (satker). With the STTAL personnel pickup lyn facility can improve the performance of personnel at each work unit, travel time to the work unit is faster than using public transportation. Updated information related to vehicles in support of personnel pick-up cannot yet be fully accessed by personnel, so misinformation often occurs. Therefore, it is necessary to design an Android-based personnel pickup lyn monitoring system application. Here we will design a device for monitoring the pickup lyn by using a transmitter device in the form of a cellphone carried by a man or driver. This system can provide information through an application that is embedded on Android by looking at an integrated application in Open Street Map, which is able to send vehicle position data through an application that is planted on the Android user so that STTAL personnel can monitor the position of pickup service vehicles and updated information related to the vehicle. worn. Users can access the application and see the pickup lyn position on the android mobile. After this system is built, it makes it easy for all STTAL personnel who use the pickup service vehicles to monitor the position of the vehicle through applications that are planted on Android. Keywords : Android, Lyn pickup personnel, Open Street Map